Multi-module intelligent glass and preparation process thereof
By adding a conductive silver paste layer and an anti-static coating in the preparation process of smart glass, and curling and forming it at high temperature, the problems of increased power consumption and insufficient shading ability caused by the electrostatic force of existing smart glass are solved, and high-quality The effect of occlusion ratio and normal expansion and contraction.
Patent Information
- Application Number
- CN202310886050.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-19
- Publication Date
- 2025-01-21
AI Technical Summary
The existence of electrostatic force between the existing smart glass causes an increase in electricity consumption, destroying the curling and expansion functions. At the same time, the light-shielding ability of the top electrode material is weak and the barrier effect is poor.
The multi-module smart glass preparation process is adopted, including compounding a conductive layer, an insulating layer, a conductive silver paste layer and an anti-static coating on the glass substrate, and curling and forming it at high temperature to ensure that there is no accumulation of static electricity between the electrodes and to improve the light-shielding ability .
It achieves a high blocking rate of visible light (more than 99%) in the light-shielding state, avoids the accumulation of static electricity, ensures the normal expansion and contraction of the film, and improves the effects of energy conservation, environmental protection, and beautiful cleanliness.
Smart Images

Figure CN119330613A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of solar energy, and in particular relates to a multi-module smart glass and a preparation process thereof. Background Art
[0002] Energy consumed by space heating and cooling accounts for a large part of the total energy consumption of buildings, and windows are the main channel for sunlight to penetrate into the space. By properly controlling the sunlight that penetrates through the windows, the energy required for space cooling or heating can be greatly reduced. Smart glass is a glass material with intelligent and dimmable properties. It can automatically adjust the degree of light penetration through the glass according to the external environment and user needs, and realize the energy management of light within the visible light range. This reduces the temperature difference between indoors and outdoors and energy consumption, which is of great significance for energy conservation and emission reduction and improving building energy efficiency.
[0003] The current smart glass can be prepared with optically transparent glass as the substrate, mainly through the electrostatic drive curling stress electrode curling and unfolding to achieve the light transmission adjustment. Most micro shutters are based on standard microelectronics manufacturing processes, such as electron beam evaporation, magnetron sputtering, optical lithography, plasma etching and deposition. The traditional single-module micro shutter preparation process is as follows Figure 1 Shown: (a) Glass substrate coated with TCO, insulating layer and sacrificial layer; (b) Patterning and etching of sacrificial layer to define anchor; (c) Top electrode deposition; (d) Patterning the geometry of micro shutters by etching the top electrode; (e) Releasing the micro shutters by removing the sacrificial layer. However, the electrostatic force between the bottom electrode and the top electrode will lead to an increase in power consumption, which will seriously undermine the journey of smart glass to curl and unfold. In addition, when the top electrode is in the unfolded state, the conventional top electrode material has weak light-shielding ability and poor energy blocking effect in space. Summary of the invention
[0004] The purpose of the present invention is to overcome the deficiencies of the prior art and provide a multi-module smart glass and a preparation process thereof. The multi-module smart glass has anti-static accumulation capability and a visible light shielding rate of more than 99% in a shading state.
[0005] In order to achieve the above object, the technical solution adopted by the present invention is:
[0006] A first aspect of the present invention provides a process for preparing a multi-module smart glass, comprising:
[0007] S1. Composite conductive layer on glass substrate;
[0008] S2. A composite insulating layer on the surface of the conductive layer obtained in S1;
[0009] S3. The composite conductive silver paste layer is dispensed on the surface of the insulating layer obtained in S2 using silver paste, and the composite antistatic coating is applied on the surface of the remaining portion;
[0010] S4. A composite metal layer on the surface of the composite layer obtained in S3, followed by a composite ink layer;
[0011] S5. The material obtained in S4 is formed into a plurality of micron-sized modules by photolithography, and then rolled into a shape at a high temperature;
[0012] S6. Connecting a wire between the conductive layer and the metal layer and connecting it to a power source;
[0013] S7. Pressing the glass material obtained in S6 into a hollow sealed glass to obtain the multi-module smart glass.
[0014] In step S1
[0015] Preferably, the visible light transmittance of the glass after compounding the conductive layer is greater than 90%.
[0016] Preferably, the conductive layer comprises an indium tin oxide (ITO) layer.
[0017] Preferably, the thickness of the conductive layer is 500-1000 nm, for example, 550 nm, 600 nm, 650 nm, 700 nm, 750 nm, 800 nm, 850 nm, 900 nm, 950 nm, etc.
[0018] Preferably, the sheet resistance of the glass after compounding the conductive layer is 100-200Ω, for example, 110Ω, 120Ω, 130Ω, 140Ω, 150Ω, 160Ω, 170Ω, 180Ω, 190Ω, etc.
[0019] In step S2
[0020] Preferably, the insulating layer has a thickness of 1-5 μm, for example, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm, etc.
[0021] Preferably, the visible light transmittance of the glass after being compounded with the insulating layer is greater than 90%.
[0022] Preferably, the insulating layer includes at least one of a SiO2 layer and a polypropylene (PP) layer; more preferably, the insulating layer includes a SiO2 layer.
[0023] In step S3
[0024] Preferably, the silver paste is a high temperature resistant nano silver paste. In the present application, the high temperature resistant nano silver paste is selected to avoid the shrinkage of the silver paste during the later high temperature curling and molding, thereby reducing the shading effect of the smart glass.
[0025] Preferably, the width of the conductive silver paste layer is 1-5 μm, and the thickness of the conductive silver paste layer is 0.5-2 μm. The silver paste layer is located at the edge opposite to the curling edge, and is used to connect the wire.
[0026] Preferably, the antistatic coating has a thickness of 0.5-1 μm.
[0027] Preferably, the sheet resistance of the antistatic layer is 10 7 -10 9 Ω, which can meet the anti-static requirements between the bottom electrode and the top electrode and ensure the smooth unfolding of the top electrode material of the curled metal layer.
[0028] Preferably, the antistatic coating used in the antistatic coating comprises, by mass percentage, 3-10% lithium ions, 15-25% polypropylene PP and the remainder solvent.
[0029] Furthermore, the solvent includes at least one of butanone (MEK), acetone (AC), cyclohexane (CH), and methylcyclohexane (MCH).
[0030] In step S4
[0031] Preferably, the metal layer includes at least one of a metal aluminum layer and a metal nickel layer.
[0032] Preferably, the thickness of the metal layer is 500-1000 nm, for example, 550 nm, 600 nm, 650 nm, 700 nm, 750 nm, 800 nm, 850 nm, 900 nm, 950 nm, etc.
[0033] Preferably, the ink layer has a thickness of 1-2 μm.
[0034] In step S5
[0035] Preferably, each of the micron-sized small modules has a length of 25-35 μm and a width of 25-35 μm.
[0036] Preferably, the gap between two adjacent micron-sized modules is 1-2 μm.
[0037] Preferably, the high temperature during the curling process is 100-180°C.
[0038] Preferably, the curling radius of the micron-sized small module after curling is 10-30 μm.
[0039] In step S7
[0040] Preferably, the hollow sealing glass is filled with gas, and the gas includes SF6 and / or Ar.
[0041] Preferably, the thickness of the hollow sealing glass is 0.5 mm-20 mm.
[0042] Preferably, the voltage of the power supply is 20-60V.
[0043] Preferably, the current of the power supply is 15-100 mA; more preferably, it is 30-100 mA.
[0044] Preferably, the composite method is selected from at least one of magnetron sputtering, spraying and coating.
[0045] Furthermore, the ITO layer, the insulating layer, and the metal layer can be composited by magnetron sputtering, and the antistatic coating layer and the ink layer can be composited by spraying, coating, and the like.
[0046] A second aspect of the present invention provides a multi-module smart glass prepared according to the multi-module smart glass preparation process.
[0047] Due to the application of the above technical solution, the present invention has the following advantages compared with the prior art:
[0048] The multi-module smart glass obtained by the preparation process of the multi-module smart glass in the present invention has the ability to prevent static electricity accumulation, and there is no static electricity accumulation between electrodes. Under the action of voltage, the film can expand and contract normally, and has a strong ability to block sunlight in the shading state, thereby achieving the characteristics of energy saving and environmental protection, space saving, smart home, beautiful and clean, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0049] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0050] Figure 1 The preparation process of the traditional single-module micro shutter;
[0051] Figure 2 A top view of the multi-module smart glass in the present application in an unfolded state;
[0052] Figure 3 A side view of the rolled-up state of the multi-module smart glass in this application;
[0053] Figure 4 Schematic diagram of the distribution of the conductive silver paste layer (shaded part) on the surface of the insulating layer of the multi-module smart glass in this application.
[0054] Description of the drawings: 1. Glass substrate; 2. Conductive layer; 3. Insulating layer; 4. Conductive silver paste layer; 5. Antistatic layer; 6. Metal layer; 7. Ink layer. DETAILED DESCRIPTION
[0055] All features disclosed in the present invention, or steps in all methods or processes disclosed, except mutually exclusive features or steps, may be combined in any manner.
[0056] In view of the deficiencies in the prior art, the inventor of this case has proposed the technical solution of the present invention after long-term research and extensive practice. The technical solution, its implementation process and principle will be further explained as follows.
[0057] The principle of the smart glass of the present invention is: a metal layer such as Al and Ni and an ITO layer are connected to a power supply, a voltage of 20-60V and a current of 15-100 mA are applied, and an electrostatic field force is generated, so that the curled film is unfolded by the electrostatic field force to play a shading role (such as Figure 2 After turning off the power, the film automatically rewinds (as shown in Figure 3 As shown in the figure, the glass becomes transparent again, which helps sunlight to enter the space through the glass.
[0058] Furthermore, in the present invention, an ink layer is compounded on the metal layer, especially a 1-2 μm thick ink layer is coated or sprayed on the Al or Ni layer, which is beneficial to increase the visible light blocking rate to more than 99%, better ensure the shading effect, and at the same time does not affect the stress performance of the Al layer or the Ni layer, so that the Al layer or the Ni layer can repeatedly and uniformly reach a certain degree of curling within a certain voltage range and unfold smoothly.
[0059] The present invention is further described below in conjunction with the examples. However, the present invention is not limited to the following examples. The implementation conditions used in the examples can be further adjusted according to the different requirements of specific use, and the implementation conditions not specified are conventional conditions in the industry. The technical features involved in each embodiment of the present invention can be combined with each other as long as they do not conflict with each other.
[0060] The experimental methods in the following examples are all conventional methods unless otherwise specified; the experimental materials used are all purchased from conventional biochemical reagent manufacturers unless otherwise specified.
[0061] Example 1
[0062] This embodiment 1 provides a multi-module smart glass, and the preparation process is as follows:
[0063] S1. Magnetron sputtering of an ITO layer on a glass substrate, with a visible light transmittance of >90%, a square resistance of 150Ω, and a thickness of 750nm after sputtering;
[0064] S2. Sputter an insulating layer on the surface of the ITO layer with a thickness of 3 μm and a visible light transmittance of >90% after sputtering;
[0065] S3. Use high temperature resistant nano silver paste to dispense glue on the surface of the insulation layer (specifically Figure 4 The shaded part in the figure has a width of 3 μm and a thickness of 1 μm. The rest of the surface is coated with an antistatic coating (specifically Figure 4 The blank part except the shaded part in the figure) has a thickness of 0.75 μm (the antistatic coating is obtained by dispersing 5% lithium ions and 20% PP materials in MEK solvent);
[0066] S4. A composite aluminum metal layer with a thickness of 750 nm is then formed, followed by a composite ink layer with a thickness of 1 μm, and a visible light blocking rate of > 99%;
[0067] S5. Through photolithography, it is formed into multiple micron-scale small modules, each of which has a size of 30μm×30μm, and a gap of 1-2μm between each small module. It is then heated and curled at a high temperature of 150°C, and the curling radius is 10-30μm;
[0068] S6. Connecting wires in the ITO layer and the metal layer, and passing a DC power switch;
[0069] S7. Use spacers (10mm) around the glass and press another piece of glass to form a hollow sealed glass filled with SF6 or Ar gas.
[0070] When powered at 40V and 50mA, the curled metal layer expands and contracts due to the electrostatic field force, achieving the functions of transparency and light shielding. In addition, the test showed no static electricity accumulation, and the film expanded and contracted normally.
[0071] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes made according to the spirit of the present invention should be included in the protection scope of the present invention.
Claims
1. A preparation process of multi-module smart glass, characterized in that: include: S1. Composite conductive layer on glass substrate; S2. A composite insulating layer on the surface of the conductive layer obtained in S1; S3. The composite conductive silver paste layer is dispensed on the surface of the insulating layer obtained in S2 using silver paste, and the composite antistatic coating is applied on the surface of the remaining portion; S4. A composite metal layer on the surface of the composite layer obtained in S3, followed by a composite ink layer; S5. The material obtained in S4 is formed into a plurality of micron-sized modules by photolithography, and then rolled into a shape at a high temperature; S6. Connecting a wire between the conductive layer and the metal layer and connecting it to a power source; S7. Pressing the glass material obtained in S6 into a hollow sealed glass to obtain the multi-module smart glass.
2. The process for preparing the multi-module smart glass according to claim 1, characterized in that: In step S3, the antistatic coating used in the antistatic coating comprises, by mass percentage, 3-10% lithium ions, 15-25% polypropylene PP and the remainder solvent.
3. The preparation process of the multi-module smart glass according to claim 1 or 2, characterized in that: In step S3, the thickness of the antistatic coating is 0.5-1 μm; And / or, in step S3, the sheet resistance of the antistatic layer is 10 7 -10 9 Ω; And / or, in step S3, the silver paste is a high temperature resistant nano silver paste; And / or, in step S3, the width of the conductive silver paste layer is 1-5 μm, and the thickness of the conductive silver paste layer is 0.5-2 μm.
4. The process for preparing the multi-module smart glass according to claim 1, characterized in that: In step S1, the visible light transmittance of the glass after compounding the conductive layer is greater than 90%; And / or, in step S1, the conductive layer includes an ITO layer; And / or, in step S1, the thickness of the conductive layer is 500-1000 nm; And / or, in step S1, the sheet resistance of the glass after compounding the conductive layer is 100-200Ω.
5. The process for preparing the multi-module smart glass according to claim 1, characterized in that: In step S2, the insulating layer has a thickness of 1-5 μm; And / or, in step S2, the visible light transmittance of the glass after being compounded with the insulating layer is greater than 90%; And / or, in step S2, the insulating layer includes at least one of a SiO2 layer and a PP layer.
6. The process for preparing multi-module smart glass according to claim 1, characterized in that: In step S4, the metal layer includes at least one of a metal aluminum layer and a metal nickel layer; And / or, in step S4, the thickness of the metal layer is 500-1000 nm; And / or, in step S4, the ink layer has a thickness of 1-2 μm.
7. The process for preparing multi-module smart glass according to claim 1, characterized in that: In step S5, each of the micron-sized small modules has a length of 25-35 μm and a width of 25-35 μm; And / or, in step S5, the gap between two adjacent micron-sized small modules is 1-2 μm. And / or, in step S5, the high temperature during the curling molding is 100-180°C; And / or, in step S5, the curling radius of the micron-sized small module after curling is 10-30 μm.
8. The process for preparing multi-module smart glass according to claim 1, characterized in that: In step S7, the hollow sealing glass is filled with gas, and the gas includes SF6 and / or Ar; And / or, in step S7, the thickness of the hollow sealing glass is 0.5 mm-20 mm.
9. The process for preparing multi-module smart glass according to claim 1, characterized in that: The voltage of the power supply is 20-60V, and the current is 15-100 mA; And / or, the composite method is selected from at least one of magnetron sputtering, spraying, and coating.
10. A multi-module smart glass prepared according to the preparation process of the multi-module smart glass according to any one of claims 1 to 9.